Fungal infections today: size of the problem and focus on the initial cost of therapy with echinocandin - Venditti, Mario (Farmeconomia. Health Economics and Therapeutic Pathways, 2010)
Three candins had been approved for the treatment of invasive candidiasis (IC): caspofungin, micafungin, and anidulafungin. Different drugs are associated with different needs for dose adjustment which might affect the total cost. A Spanish economic analysis estimated the budget impact of caspofungin, micafungin and anidulafungin in the treatment of 100 patients with invasive candidiasis from the perspective of the Spanish hospital pharmacy setting. It has demonstrated that patients treated with anidulafungin did not required dose adjustment unlike caspofungin and micafungin, and the use of anidulafungin in the treatment of adult non-neutropenic patients with invasive candidiasis is a cost saving treatment option, from the pharmacy department perspective in Spain. The aim of this study was to estimate the initial costs of therapy with caspofungin, micafungin, and anidulafungin in the perspective of the Italian hospital setting.